Development of a novel dual reproductive organ on a chip: recapitulating bidirectional endocrine crosstalk between the uterine endometrium and the ovary. (16th October 2020) - Park, Se-Ra; Kim, Soo-Rim; Lee, Jin Woo; Park, Chan Hum; Yu, Wook-Joon; Lee, Seung-Jin; Chon, Seung Joo; Lee, Dae Ho; Hong, In-Sun
Abstract: Conventional 2D or even 3D in vitro culture models for human reproductive organs cannot properly recapitulate the bidirectional endocrine crosstalk between the uterine endometrium and the ovary. This crosstalk is essential for maintaining the various physiological features and functions of each tissue. Moreover, most in vitro models for the female reproductive tract also fail to mimic its multicellular structure. We therefore developed a novel 'dual reproductive organ on a chip' that reflects the bidirectional endocrine cross-talk and the complex multicellular structures by integrating various cellular components of both the human uterine endometrium and the ovary with several biodegradable natural polymers. Indeed, the bidirectional endocrine crosstalk between these two tissues is achieved through media sharing between channels, and it can markedly improve the viability of loaded cells within each chamber of the chip platform. In addition, we also identified a reliable reproductive toxicity marker, SERPINB2, which is significantly increased in response to various toxic exposures in both endometrial and ovarian follicular cells. Based on these findings, we next established a SERPINB2 luciferase reporter system that was specifically designed for detecting and quantifying the toxicity of certain substances. By introducing this SERPINB2 luciferase reporter system into the loaded cells within the chip platform, we ultimately developed an effective 'dual reproductive organ-on-chip' that was successfully used to predict the reproductive toxicity of various hazardous materials.